Before things fall apart: The role of the Soviet Union in Somalia’s troubled past (1969-1978)/ Hassan Sheikh Ali Nur Muhammad, Muhammad Danial Azman and Roy Anthony Rogers - Muhammad, H.S.A.N.; Azman, Muhammad Danial; Rogers, Roy Anthony (IIUM Press, 2017)
The narrative of Somalia as ‘a nation without a state’ has been central to analyses seeking to explain state failure, the absence of Weberian political authority, civil war, and the resurgence of radical Islamisation and terrorist networks. While the popular depiction on the causes of state collapse has focused on either external or internal factors, this article shows that the socio-political construction of post-independent Somalia has been more contested than frequently depicted, even before the foreign intervention. It argues that foreign intervention exacerbated the existing inability of the government to build standard state building institutions, and created further diffi culties in forging nation-building. By revisiting the immediate post-colonial period of Somalia under the Soviet Union’s infl uence (1969-1978), the aim of this article is not to suggest that we should neglect the internal factors for Somalia’s troubled past, but to highlight the destructive consequences of foreign interventions (as an external factor) on post-colonial state-building. It provides further incentives for internal factors to become more pervasive in challenging contemporary international attempts to restore political order in Somalia.